Studies on the Dormancy-Awakening and -Breaking in the Two-Rowed Barley Seed : III. The dormancy-awakening of seeds obtained from plants affected by flooding and lodging during the ripening period - MABUCHI, Toshio (Japanese Journal of Crop Science, 1993)
Effects of flooding and lodging on the seed dormancy were studied in the two-rowed barley seed. Seeds were obtained from plants which were subject to the flooding treatment 4 times during the ripening period and from lodged plants which showed a lodging index of 4. Awakening from seed dormancy in this crop was closely related with the thickness of the seeds. Awakening from seed dormancy occurred earliest in seeds with a thickness over 2.8 mm, followed by seeds with thicknesses of 2.5-2.6 mm and 2.2-2.4 mm. Similarly, dormancy-awakening was clearly related to 1000 kernel weight and to germination percentage with the heavier grains awakening earlier from dormancy. When the ratio of large grain was reduced, maturation was inhibited. Analysis of the photosynthetic activity of awns during the ripening process of plants treated with flooding was based on 14CO2 levels. It was clear that the photosynthetic ability in the upper position of the ear of awns was lowered by flooding. These results suggest that flooding and lodging have an indirect effect on seed dormancy-awakening on two-rowed barley.